塑料门窗三点直线布置热熔焊接机的设计与研究 - 刘有余; 张浩; 朱慧萍; 叶文刚; 韩江 (Jixie chuandong)
To enhance the quality,the yield and the universal application of plastic door and window,an advanced hot-melt welding machine of three-position linear arrangement for plastic door and window is designed based on new principles.The overall program planning is put forward.The principle of locating and clamping and the operating principle of some key phases are researched.The design methods of some key mechanical components are expound.Finally,type selection calculation of cylinder and its pressure determination are introduced.Some crucial problems in the development process are solved,the automation and the reliability of the machine are enhanced.